Remarks on the genus Diaphanogryllacris Karny, 1937 (Orthoptera: Gryllacrididae) from China with two new species - Lv, Wenqing; Duan, Yueting; Shi, Fuming (Zootaxa, 2025)
This paper reports 2 new species of the genus Diaphanogryllacris Karny, 1937 from China, i.e. Diaphanogryllacris conica sp. nov. and Diaphanogryllacris taiwanis sp. nov., morphological photographs of the new species with 5 known species of the genus are provided. The all specimens are deposited in the Museum of Hebei University, Baoding, China.